Multi-Cavity Collection: A Method for Sampling Bulk Solutions from Plug Media - Jianjun Chen; Yangfeng Huang; Cynthia A. Robinson; Russell D. Caldwell (EDIS)
This document is ENH855, a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Science, University of Florida. First published: December 2001.